Lost in Space: Physically, Virtually, and Pedagogically - Westberry, N; McNaughton, S; Billot, J; Gaeta, H (Higher Education Research and Development Society of Australasia (HERDSA), 2013)
A wide range of literature reveals the pervasive and directing influence that physical and virtual spaces and the role of place have on teaching practice, and the need to better understand these influences. The experiences of teachers transitioning into new spaces, pedagogies and practices has been under-researched, particularly when learning spaces do not work as expected. This paper reports on a study that aimed to provide ground-level views of teachers’ experiences in redesigned lecture spaces that incorporated videoconferencing technology. Using an ethnographic approach, the on-going activities of the teachers using the video conferencing were obtained through video recordings, individual accounts, and interview and focus group dialogues. This paper examines how teachers were able to harness these changed lecture spaces to produce what they perceived to be effective learning places. It considers the factors that affected the transformation of the space into a place for teaching and learning, showing how teachers often felt physically, virtually, and pedagogically lost in this changed learning space. We argue that the disconnection from students that visually-mediated and virtual teaching brings has not been sufficiently addressed from a pedagogical perspective. The understanding of how academics make sense of these new spaces and the ways the spaces shape those practising within them needs more focused investigation before the potential of new technologies to create effective places can be realised.
Keywords: Video conferencing; Learning spaces; Teaching spaces